2010
DOI: 10.4103/1995-705x.76801
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial fat and its association with cardiovascular risk: A cross-sectional observational study

Abstract: Background:The association between visceral obesity and cardiovascular risk has been well described. Some studies show a proportional relationship between the presence of visceral obesity and epicardial fat. Measuring the amount of epicardial adipose tissue (EAT) can be a novel parameter that is inexpensive and easy to obtain and may be helpful in cardiovascular risk stratification. However, the relationship between epicardial fat and cardiac function and that between epicardial fat and cardiac risk factors is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…These include increased ventricular stiffness, inflammation mediated by adipokines, direct lipotoxicity or a metabolic effect mediated by insulin resistance [9]. Diastolic dysfunction has been previously shown to correlate with duration of diabetes, HbA1c and obesity [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include increased ventricular stiffness, inflammation mediated by adipokines, direct lipotoxicity or a metabolic effect mediated by insulin resistance [9]. Diastolic dysfunction has been previously shown to correlate with duration of diabetes, HbA1c and obesity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data shows that diabetes is an independent risk factor predictive of LA enlargement and dysfunction. Data has also linked epicardial fat to LA and ventricular functional changes [9], and to increased LA volume [10, 11]. A highly powered analysis using a Framingham cohort demonstrated that this association is independent of other measures of adiposity in men [11].…”
Section: Introductionmentioning
confidence: 99%
“…Epicardial fat correlates with BMI and is increased in obese subjects 3 . The association of increased EFV with diastolic dysfunction may be confounded by factors such as metabolic syndrome 4,24 and hypertension 25 which are often present in obese individuals. Furthermore, increased epicardial fat appears to be related to increased atherosclerotic plaque burden, concomitant coronary artery disease, myocardial ischemia and subclinical microvascular dysfunction which is commonly seen in diabetics and in individuals with metabolic syndrome 3,5,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Several thresholds have been proposed to indicate increased cardiovascular risk 4 . However, the reproducibility of this method is imperfect, probably because these measurements only represent one planar dimension which is subject to the probe angulation, adequate visualization of the cardiac structure and the given phase of the cardiac cycle chosen to be measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation